Implementasi Kepemimpinan Pendidikan Dalam Peningkatan Mutu Pendidikan di Sekolah Melalui Melalui Sistem Nilai - Bakti Toni Endaryono (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2019)
In improving the quality of education at the school level one of them is educational leadership because it is one of the strategies that determine the emergence of changes in institutions to a better one. leadership must be improved in quality from time to time to advance the world of education at the national level through a system of values. In order for educational goals to be realized in the era of industrial revolution 4.0. Because there is still a lot of education in schools that is implemented poorly because it does not see national education quality standards, the Quality of National Education will be measured through the attainment of all National Education Standards, including standards of content, process, competency, education and education, facilities and infrastructure education funding and assessment (PP RI No. 19 of 2005).One element of the quality of educational institutions is the quality of services carried out by these institutions to their stakeholders. the quality of service is part of the implementation of TQM education that is implemented by the leadership of the institution to its customers, so that in improving the quality, educational institutions must have several elements such as Tangible, intangible, Reliability, Responsive institution. Public leadership is related to the ability to establish cooperation and become a reference for the public with functional and operational management systems including planning, organizing, staffing, leading, controlling in internal and external activities, with reference to the vision and mission of the institution.